PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KINERJA PERUSAHAAN - Kusumawati, Ratih; Nuswantara, Dian Anita (Journal of Innovation Research and Knowledge, 2023)
This research aims to look into the impact of the characteristics of audit committee on company performance. The sample consists of companies that were listed on the LQ45 Indonesia Stock Exchange (IDX) respectively around 2016 and 2020. The findings indicate that committee size and frequency of meeting have a notable negative relationship with firm performance, whereas expertise have quite a significant positive relationship. This study also unveil that independence possess insignificant association with performance of companies. This study’s findings may assist managers and boards determine the most appropriate choices about the audit committee characteristics to enhance the company’s audit committee for implementation in future policy preparation to protect shareholders’ preferences. This study adds to the literature by identifying the role of audit committee characteristics in company performance, attempting to argue that specific audit committee characteristics drive performance.